Application of restriction fragment length polymorphism (RFLP) and high resolution melting (HRM) analysis of beta-tubulin gene for species and strains differentiation in Trichophyton mentagrophytes species complex. Issue 3 (September 2016) - Sun, Pei-Lun; Lin, Hsin-Chieh; Hsiao, Pa-Fan; Lu, Jang-Jih
Highlights: Anthropophilic and zoophilic strain of T. interdigitale are morphologically identical. Precise identification of these two strains is clinically important. Partial beta-tubulin gene is an ideal region for strain differentiation. Combined RFLP and HRM analyses of partial beta-tubulin gene can discriminate these two strains.